1995
DOI: 10.1021/ma00105a012
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Conformation Entropies of Dimer Liquid Crystals and Comparison with the Observed Transition Entropies at Constant Volume

Abstract: RIS analysis of the deuterium quadrupolar splitting data was performed for a,a»-bis [(4,4'cyanobiphenylyl)oxy]alkane dimer liquid crystals having -0(CH2)"0flexible spacers (n = 9 and n = 10 (CBA-10)) between the 4,4'-cyanobiphenylyl ends according to the scheme previously established. The analysis indicates that most of the conformers involved in the range 0 < if i,if 2 < 45°a dopt spatial configurations reasonably consistent with the nematic arrangement of mesogenic cores in both dimer LC systems, where ifi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 7 publications
3
17
0
Order By: Relevance
“…To test this hypothesis, Blatch et al [74] studied two series of chiral dimers, one symmetric (S)2 MB.OnO. (S)2MB, 21 and the other non-symmetric, CBOnO. (S)2MB, 22 For the CBOnO.…”
Section: Chiral Liquid Crystal Dimersmentioning
confidence: 99%
“…To test this hypothesis, Blatch et al [74] studied two series of chiral dimers, one symmetric (S)2 MB.OnO. (S)2MB, 21 and the other non-symmetric, CBOnO. (S)2MB, 22 For the CBOnO.…”
Section: Chiral Liquid Crystal Dimersmentioning
confidence: 99%
“…We designated these dimers BPA-n, which consist of both a flexible even-number polymethylene spacer of varying length (n= 8,10,12,14,16,18,20) and two terminal mesogens. Since the nematic-isotropic transition temperatures of the dimers with even numbers less 326 than n = 8 were so high that the precise thermodynamic quantities could not be obtained, they were not dealt with here.…”
mentioning
confidence: 99%
“…In the studies mentioned hereafter, detailed analyses were mostly carried out for oligomeric LCs. The knowledge gained through studies on the low DP analogs has been found useful in understanding the spatial arrangements and thermodynamic properties of polymer LCs [12,13].…”
Section: Dependence Of Thermodynamic Properties On Degree Of Polymerimentioning
confidence: 99%
“…The integrated distribution curves of the disorientation angle θ between the two successive mesogens (P(θ) À θ) were calculated for spacers comprising odd and even numbers (n) of methylene units in the isotropic conformation [13,22]. Definition of θ and the bond angles of the linking group (X) adopted in these calculations are shown in Fig.…”
Section: Ris Analysis Of the Orientational Correlation Of The Neighbomentioning
confidence: 99%
See 1 more Smart Citation